The PKC/NOX/ROS and PYK2/MEK/ERK/PARP signalling pathways drive TRPM2 channel activation induced by non-cytolytic oxidative stress in microglial cells - Syed Mortadza, Sharifah Alawieyah; Mohamad Zahir, Nur Zulaikha; Wei, Chew Tze; Jiang, Lin Hua (Taylor and Francis, 2025)
Objectives: The study aimed to investigate the signalling mechanism for TRPM2 channel activation by non-cytolytic oxidative stress in microglia. Methods: Microglia from wild-type (WT) and TRPM2-knockout (KO) mice were exposed to 10-30 mM H2O2 for up to 24 hours. Morphological changes characteristic of microglial activation, [Ca2+]c, ROS generation and the effects of inhibiting particular signalling pathways were examined. Results: Exposure of WT microglia to H2O2 for 24 hours caused no cell death but induced salient morphological changes, which was prevented by TRPM2-KO. Exposure of WT microglia to H2O2 to 2 hours failed, and extension to 8 hours was required, to induce an increase in [Ca2+]c, which was abolished by TRPM2-KO. Exposure of microglia to H2O2 for 8 hours induced ROS generation, which was suppressed by inhibition of PKC and NADPH oxidases (NOX). H2O2-induced PARP activation in TRPM2-KO cells was lower than that in WT cells. Furthermore, H2O2-induced activation of PARP and TRPM2 and morphological changes were attenuated by inhibition of PCK and NOX as well as PYK2 and MEK/ERK. Conclusion: Our results support that PKC/NOX-mediated ROS generation and TRPM2-mediated Ca2+-induced activation of the PYK2/MEK/ERK pathway form a positive feedback mechanism to drive TRPM2 channel activation by non-cytolytic oxidative stress.